National Defense and Economic Development: Examining the Relationship Between National Defense Capability, Defense Economics, and Economic Stability - Badia Ni Partahi Nainggolan; Priyanto; Suwito; R. Djoko Andreas Navalino; Guntur Eko Saputro (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This study explores the relationship between national defense capability, defense economics, and economic stability in Indonesia’s development context. Defense and economic development are closely linked and essential for maintaining national sovereignty and prosperity, particularly amid globalization and complex geopolitical dynamics. Using a literature review and meta-analysis, the study examines how defense capability and defense economics interact to influence economic stability and growth. The findings indicate that stronger defense capability supports the defense economy, which in turn contributes to overall economic stability. However, this relationship is not linear and depends on factors such as government policy, R&D investment, domestic industrial capacity, and geopolitical conditions. Technological innovation and defense industry development are also identified as key drivers of growth and resilience to external shocks. The study provides insights for policymakers and industry stakeholders to strengthen synergy between defense and national economic development.